2015
DOI: 10.1111/1756-185x.12735
|View full text |Cite
|
Sign up to set email alerts
|

Survey on management strategies of rheumatoid arthritis in Saudi Arabia: a Saudi Society for Rheumatology Initiative

Abstract: This survey has highlighted many areas of improvement in the practice of rheumatologists in Saudi Arabia and should be the focus of future educational activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…Methotrexate is considered the standard of care in guidelines for RA management on both sides of the Atlantic and is a commonly adopted strategy among the majority of rheumatologists in Saudi Arabia and the Eastern Mediterranean region . Rheumatologists tend to push patients to continue MTX because MTX monotherapy or MTX‐based DMARD combination therapy is the first step for patients with moderate to severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate is considered the standard of care in guidelines for RA management on both sides of the Atlantic and is a commonly adopted strategy among the majority of rheumatologists in Saudi Arabia and the Eastern Mediterranean region . Rheumatologists tend to push patients to continue MTX because MTX monotherapy or MTX‐based DMARD combination therapy is the first step for patients with moderate to severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…When asked about the factors that most influence treatment selection; route of administration (70%), evidence available in the literature (61%), underlying comorbidities (61%), and patient choice (59%) were the most selected options. 23 This behavior, of engaging patients in their treatment decisions, might improve treatment-related outcomes and compliance. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Similar results were detected in a previous study regarding the management strategies adopted by rheumatologists in Saudi Arabia. 15 According to a systematic review of 19 trials published in 2009, it showed no statistically significant difference of methotrexate alone or in combination with other non-biologic DMARDs. 16 Our data reveal that more than half of the patients had inadequate response to csDMARDs.…”
Section: Discussionmentioning
confidence: 99%